Implementasi Manajemen Risiko dalam Pengelolaan Administrasi Sekolah di SD IT Adzkia 3 Padang - Nurul Hayati; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
The implementation of risk management in school administrative management constitutes a strategic measure to prevent operational errors and enhance the quality of educational governance. Poorly organized administration can give rise to various risks, including record-keeping errors, delays in reporting, and weak work accountability. This study aims to describe the application of risk management through administrative evaluation activities at SD IT Adzkia 3 Padang. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation involving the school’s administrative staff. The findings indicate that risk management is implemented through routine monthly and quarterly evaluations that focus on accuracy, orderliness, and work efficiency. The adoption of the digital e-Letter system in managing correspondence and school documents has proven effective in reducing the risk of archive loss, data input errors, and in accelerating internal communication processes. Continuous evaluation fosters the development of a professional, disciplined, and accountable work culture. Thus, the implementation of risk management at SD IT Adzkia 3 Padang not only strengthens the school’s administrative system but also serves as a crucial instrument for improving the quality of educational management.